Easy way to split the middle term in a quadratic equation to know its factorors.
If in a quadratic equation
x2 - 5x -36 =0 ,
- 36x2 has to be factorised such that the factors when added or subtracted give the answer as - 5x
the factors are - 9x & +4x, i.e when -9x & +4x, are multiplied we get -36x2 and when they are subtracted we get -5x.
therefore nthe equation in the factor form is written as
x2 - 9x +4x -36 =0 ,
x(x-9) +4(x-9) =0
(x - 9)(x +4) =0 are the factors of the given quadratic equation.
You have rated this answer /10